The Detection of TB Lungs with Microscopic and the Rapid Molecular Test Methods - Fifi Isti Tamtyas; Chylen Setiyo Rini (Medicra (Journal of Medical Laboratory Science/Technology), 2020)
Mycobacterium tuberculosis is a cause of tuberculosis (TB ) disease. In this research Mycobacterium tuberculosis can be detected using the Microscopic and Real-Time PCR. This research aims are to know the difference in the results of the examination Mycobacterium tuberculosis with microscopic method and Real-Time PCR. This research used an experimental research design and was tested using the Chi Square test. This results showed at significant difference (p=0.000) detection of pulmonary TB disease by microscopic and Real-Time PCR methods